AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN LISTENING “ANALYTICAL EXPOSITION TEXT” AT SMK NEGERI 6 DUMAI - Luki Hardianti; Atni Prawati; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study was purposively intended to analyze the difficulties of senior high students’ challenges in listening analytical exposition text. Comprehending factual information by listening to the audio was considered difficult for secondary students of SMKN 6 Dumai. This study used descriptive quantitative. The data was analyzed using a Likert-scale of listening difficulties questionnaire and listening test. 60 students of second year level were used as samples in this research. The findings showed that the level of listening skills of second-year learner own mostly is poor and caused by several causes such as minimum time to practice, word capacity, and native speaker accent.Keywords: Analysis, Listening Difficulties, Analytical Exposition Text.